Characterization of the institutionalization of pharmaceutical services in Brazilian primary health care - Gisélia Santana Souza; Ediná Alves Costa; Rafael Damasceno de Barros; Marcelo Tavares Pereira; Joslene Lacerda Barreto; Augusto Afonso Guerra Junior; Francisco de Assis Acurcio; Ione Aquemi Guibu; Juliana Álvares; Karen Sarmento Costa; Margô Gomes de Oliveira Karnikowski; Orlando Mario Soeiro; et al. (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To characterize the current stage of the institutionalization of pharmaceutical services in Brazilian cities. METHODS This study is part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines), a cross-sectional, exploratory, and evaluative study composed by an information survey in a representative sample of cities, stratified by Brazilian regions. We interviewed municipal secretaries of health, responsible for pharmaceutical services, and pharmacists responsible for the dispensing of medicines. The variables selected from the interviews were grouped into five dimensions that defined three stages of pharmaceutical services institutionalization: incipient (0%-34.0%), partial (35.0%-69.0%), and advanced (70.0%-100%), estimated based on the interviewees' answers. Frequencies were estimated with 95% confidence intervals. For the statistical association analysis, the Chi-square test was applied, with significance level of p<0.05. RESULTS Our results show a partial and heterogeneous process of institutionalization of pharmaceutical services in Brazil, and an advanced stage in formal structures, such as the municipal health plans and the existence of a standardized list of medicines. The analysed variables in the "organization, structure, and financing" dimension configured stages that range from partial to advanced. The management presented partial institutionalization, positively showing the existence of computerized system, but also disparate results regarding the autonomy in the management of financial resources. Indispensable items related to the structure expressed disparities between the regions, with statistically significant differences. CONCLUSION The study showed a partial and heterogeneous process of institutionalization of pharmaceutical services in Brazilian cities, showing regional disparities. Variables related to the normative aspects of institutionalization were positively highlighted in all dimensions; however, it is necessary to conduct new studies to evaluate the institutionalization of pharmaceutical services' finalistic activities.